Respon pertumbuhan dan produksi tanaman kacang tanah (arachis hypogaea l.) Terhadap pemberian kompos batang jagung dan pupuk organik cair limbah ampas tebu - Gepin Sianipar; Asmah Indrawati; Abdul Rahman (Universitas Medan Area, 2020)
Peanutes is one of stupple food in Indonesia leading to significant role in national crop. This research is conducted by group Random Draft (RAK) factorial consisting of 2 treatment factors: factor I: Compost stem of corn consists and factor II: Liquid Organic Fertilizer waste sugar cane. The parameters were both representing physiology and production. The results of this research are as follows: the introduction of compost corn stem is not real against the several physiology parameters. The best treatment is at a dose of 250 ml/L (T1) on the parameters of high crop, number of branches, age of flowering, production weight per sample and the production weight per Plot. The treatment of combination of corn stem compost and Liquid Organic Fertilizer from the affected sugar cane is not real on the parameters of crop height, number of branches, age of flowering, production weight per sample, number of pods per sample, and production weight per plot. The best treatment is the delivery of compost rod corn dose 1.5 kg/Plot and Liquid Organic Fertilizer of AmpasTebu dose 750ml/L.